Understanding the occurrence of Salmonella in irrigation water used to grow fresh produce in the United States, Mexico, and Canada : a systematic review and meta-analysis - Subedi, Yashoda (Kansas State University, 2022)
While there are several sources of contamination, irrigation water (groundwater and surface water sources) is an important source of fruit and vegetable contamination where Salmonella is the leading bacterial cause of fresh produce-related outbreaks in the United States. The goal of this systematic review and meta-analysis is to better understand the occurrence and potential indicators for estimating the presence of Salmonella in irrigation waters used to grow fruits and vegetables consumed in the U.S. The research questions identified for this research were 1) What is the occurrence of Salmonella in irrigation water used for fresh produce production in the U.S., Mexico, and Canada?; 2) Is there one or a combination of biological, physical, or chemical indicators that can be used to predict the occurrence of Salmonella in irrigation water used for fresh produce production in the U.S., Mexico, and Canada?; 3) Is there any regional climate effect on the occurrence of Salmonella in irrigation water sources?; and 4) Is there any difference in the occurrence of Salmonella in flowing and non-flowing surface water? As part of the systematic review process, peer-reviewed research publications that report the occurrence of foodborne pathogens in irrigation waters used for fresh produce production were identified. While 6248 articles were identified, there were only 30 that evaluated the presence of Salmonella. From these 30 articles, data were extracted, synthesized, and analyzed. The occurrence of Salmonella and potential water quality indicators (i.e., generic Escherichia coli, water temperature, pH, and precipitation events) in surface water and groundwater sources across Canada, Mexico, and the U.S. were also evaluated. Out of 30 studies, 22 were conducted in the U.S., five in Mexico, two in Canada, and one in the U.S. and Mexico. The majority of data extracted were for ponds (33 different ponds), followed by groundwater (13 different sites), irrigation channels (13 different channels), rivers (nine different rivers), creeks (four different creeks), irrigation ditches (three ditches), basins (three basins), and streams (two streams). The occurrence of Salmonella varied across surface water sources, from undetected to 100%. The highest median occurrence was reported for basins, ranging from 23.9% to 100%. The lowest was observed in groundwater where Salmonella was not detected in nine groundwater sources out of a total of 13 but was detected in four, with an occurrence up to 7%. The occurrence of Salmonella across climate regions varied with a range of undetected to 100% in U.S. Southeast, undetected to 64.6% in U.S. West, undetected to 91.7% in U.S. Northeast, undetected to 100% in U.S. South, undetected to 14.3% in Canada West North Central, undetected to 8.6% in Canada Northwest, and undetected to 66.7% in Mexico West. Salmonella occurrence was significantly lower in non-flowing surface water in the U.S. West compared to water sources in the U.S. Southeast, either non-flowing (P=0.0040) or flowing surface water (P=0.0015). Further, ten studies analyzed the association between the presence of Salmonella and generic E. coli, of which four reported a positive association and six found no association. The highest mean concentration of generic E. coli (4.61 log CFU/100ml) was reported in irrigation channels in the West climate region in Mexico where Salmonella was present in 36.4% of samples evaluated. The water quality standard (2.1 log CFU/100ml for generic E. coli) specified by the Food Safety Modernization Act's Produce Safety Rule was exceeded in four studies conducted in the United States, two in Canada, and one in Mexico, with a range of 2.11 log CFU/100ml- 4.61 log CFU/100ml for generic E. coli. Through this study’s synthesis of available data, the impact of water source or climate region on the occurrence of Salmonella could not be determined. Further, conclusions could not be made on the potential of water quality indicators as indicators for the presence of Salmonella in irrigation water. While the initial research questions could not be answered, this review and synthesis has provided recommendations for the design of environmental public health studies (e.g., methodological approach, minimum reporting, and sharing of experimental details) needed to address complex questions like those posed in this study. With the proper approach to future irrigation water studies, a systematic review and meta-analysis could provide significant insights to inform policies for the safe production of produce.
Keywords: Salmonella; Irrigation water; Fresh produce; Systematic review